2021
DOI: 10.3389/fmed.2020.616524
|View full text |Cite
|
Sign up to set email alerts
|

Management of Staphylococcus aureus Bloodstream Infections

Abstract: Staphylococcus aureus bloodstream infections are associated with a high morbidity and mortality. Nevertheless, significance of a positive blood culture with this pathogen is often underestimated or findings are misinterpreted as contamination, which can result in inadequate diagnostic and therapeutic consequences. We here review and discuss current diagnostic and therapeutic key elements and open questions for the management of Staphylococcus aureus bloodstream infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 81 publications
0
22
0
1
Order By: Relevance
“…Bacterial infections are the result of pathogenic bacteria entering and multiplying in the human body; these are a major deleterious factor in some infections ( Anderson and Kendall, 2017 ; Martin and Bachman, 2018 ). For example, the gram-positive bacterium Staphylococcus aureus is a human pathogen ( Kimmig et al, 2021 ) that is constantly a source of skin infections, lung infections, gastroenteritis, and urinary tract infections ( Thomer et al, 2016 ; Del Giudice, 2020 ). Over the years, researchers have observed that antibacterial substances can be isolated from endophytic fungi of various medicinal plants ( Pinheiro et al, 2017 ; Nischitha and Shivanna, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections are the result of pathogenic bacteria entering and multiplying in the human body; these are a major deleterious factor in some infections ( Anderson and Kendall, 2017 ; Martin and Bachman, 2018 ). For example, the gram-positive bacterium Staphylococcus aureus is a human pathogen ( Kimmig et al, 2021 ) that is constantly a source of skin infections, lung infections, gastroenteritis, and urinary tract infections ( Thomer et al, 2016 ; Del Giudice, 2020 ). Over the years, researchers have observed that antibacterial substances can be isolated from endophytic fungi of various medicinal plants ( Pinheiro et al, 2017 ; Nischitha and Shivanna, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is responsible for both healthcare- and community-associated infections ( 41 , 42 ). Infections are treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…After E. coli , S. aureus is among the leading causes of hospital‐ and community‐acquired endovascular infections 7,137 . Intravascular catheters are an important source of S. aureus bacteremia and removal of these indwelling devices commonly resolves infections; 138 however, once the pathogen gains access to the cardiovascular system, secondary complications can occur.…”
Section: S Aureus Bacteremiamentioning
confidence: 99%